Necesidad de otorgar facultades al juez de trabajo para que dicte medidas cautelares de carácter real en la fase de ejecución de la sentencia en los juicios de trabajo, para garantizar el pago de la indemnización del trabajador - ENRIQUEZ LOMBEIDA, JOSE FRANCISCO (2015)
If we admit that human beings are social by nature , we must also accept that in any union between individuals can be given conflict . The sharing of experiences entails the diversity of opinions , and in many cases , this plurality confrontation arises . When configured as something inherent in human beings , that is, it is in their nature . From the first groups of humans we find leaders in charge , among other things, to resolve conflicts arising between community members . At work the fictions that may occur in labor relations are the differences that may arise between workers and employers , only between that or just between them , arising out of or following the birth , modification or enforcement of individual or collective relationships work . This situation described above is precisely the process of the labor process , pending before the labor courts , which seek them become effective payment of employees and compliance with other rights , which have been systematically broken is the employer. Precautionary or protective measures , which seek to protect a right , so this is not violated , in the field of labor trial these precautionary measures are not presented , so that the lack of these can cause the rights being affected workers. This violation has transcended to such an extent that affects the effectiveness of the judgment issued in the trial , failing to enforce the right of the person affected by the above, the purpose of this thesis is to demonstrate the importance who have legally grant the right to a judge for an injunction real character in the implementation phase of the judgment in the trials of work, to ensure payment of worker's compensation.